Determination of the ratio of b-quark fragmentation fractions fs/fd in pp collisions at √s = 7 TeV with the ATLAS detector - Aad, Georges; Anders, Christoph; Andrei, George Victor; Baas, Alessandra Edda; Brandt, Oleg; Djuvsland, Julia Isabell; Dunford, Monica; Geisler, Manuel Patrice; Hanke, Paul; Jongmanns, Jan; Kluge, Eike-Erik; Kugel, Andreas; et al. (Physical review letters, 2015)
With an integrated luminosity of 2.47  fb−1 recorded by the ATLAS experiment at the LHC, the exclusive decays B0s→J/ψϕ and B0d→J/ψK*0 of B mesons produced in pp collisions at √s=7  TeV are used to determine the ratio of fragmentation fractions fs/fd. From the observed B0s→J/ψϕ and B0d→J/ψK*0 yields, the quantity (fs/fd)[B(B0s→J/ψϕ)/B(B0d→J/ψK*0)] is measured to be 0.199±0.004(stat)±0.008(syst). Using a recent theory prediction for [B(B0s→J/ψϕ)/B(B0d→J/ψK*0)] yields (fs/fd)=0.240±0.004(stat)±0.010(syst)±0.017(th). This result is based on a new approach that provides a significant improvement of the world average.